BIR-1, a Caenorhabditis elegans homologue of Survivin, regulates transcription and development - Kostrouchova, Marta; Kostrouch, Zdenek; Saudek, Vladimir; Piatigorsky, Joram; Rall, Joseph Edward (Proceedings of the National Academy of Sciences of the United States of America, 2003)
bir-1, a Caenorhabditis elegans inhibitor-of-apoptosis gene homologous to Survivin is organized in an operon with the transcription cofactor C. elegans SKIP (skp-1). Because genes arranged in operons are frequently linked functionally, we have asked whether BIR-1 also functions in transcription. bir-1 inhibition resulted in multiple developmental defects that overlapped with C. elegans SKIP loss-of-function phenotypes: retention of eggs, dumpy, movement defects, and lethality. bir-1 RNA-mediated interference decreased expression of several gfp transgenes and the endogenous genes dpy-7 and hlh-1. Immunoblot analysis revealed decreased phosphoacetylated histones in bir-1 RNA-mediated interference-treated worms. In a heterologous transfection system, BIR-1 augments thyroid hormone-regulated transcription and has an additive effect with SKIP. These results show that BIR-1 functions in the regulation of transcription and development.
Keywords: Cell Line; apoptóza; vývojová regulace genové exprese; RNA interference; imunohistochemie; hormony štítné žlázy; buněčné dělení; Cell Division; RNA Interference; Thyroid Hormones; Transcription, Genetic; genetická transkripce; western blotting; Gene Expression Regulation, Developmental; histony; Blotting, Western; Immunohistochemistry; Histones; zvířata; Humans; proteiny Caenorhabditis elegans; Caenorhabditis elegans; acetylace; buněčné linie; Acetylation; Caenorhabditis elegans Proteins; lidé; Apoptosis; Animals